Professional training for intervention in aberrant behavior: Development of teaching materials and social validation - Yazawa, Thais [UNESP]; Fornazari, Sílvia Aparecida [UNESP] (Universidade Federal do Paraná, 2019)
People with severe intellectual disabilities are usually overlooked in what concerns specific care services despite the policies of school and social inclusion aimed at them. These individuals may present aberrant behaviors, a set of maladaptive behaviors which is likely to stigmatize and put these people aside from society, then complicating inclusion and specific treatment. Thus, the present paper aimed to develop and socially validate an instruction material by using basic principles of Behavior Analysis in order to decrease the display of aberrant behaviors and increase the frequency of behaviors appropriate to the context of health professionals who provide treatment for people with severe intellectual disabilities. The instruction material was addressed to 11 health professionals, who performed the activities proposed therein. Then, the participants were applied the Therapy Attitude Inventory (TAI), adapted in order to foster the social validation of the material, in which 80% of the participants appraised the material as above average. These results were also shown in TAI's correlation and in the final interview. Participants assessed that the material helped them understand the behavior and appropriately intervene in it.
Capacitação de profissionais para intervenção em comportamentos aberrantes: Elaboração de material didático e validação social
Keywords: Aberrant behaviors; Behavior analysis; Instruction material; Special education